Разработка автоматизированной системы для видеодерматоскопии - Исаева, О. А.; Аврунін, О. Г. (ХНУРЕ, 2019)
The work is devoted to the development of an automated system for video dermatoscopy. The main approaches to the design of such systems, methodological support and structural modules are considered. The main stages of digital processing of dermatoscopic images are proposed. The main focus is on the methods of automated segmentation of dermatoscopic images and the analysis of the errors that arise. The diagnostic capabilities of the digital dermatoscopy method are discussed.
Keywords: система автоматизированная; видеодерматоскопия